Percepções dos profissionais de saúde em relação aos cuidados paliativos no contexto da atenção primária à saúde - Sartori, Kamila Pena (2022)
Objective: To analyze the perceptions of professionals working in Primary Health Care in relation to Palliative Care. Materials and Methods: this is an exploratory and qualitative study, carried out with Primary Health Care workers from a municipality in the interior of the state of São Paulo (high school, technical and higher education level) who agreed to participate in the research. Data collection was carried out through semi-structured interviews, following a script with guiding questions. This stage began after approval of the research project by the Research Ethics Committee of the Federal University of São Carlos. The recordings were heard repeatedly, so that there was no doubt about the content and so that the speech was fully transcribed. After this step, the transcribed narratives were validated individually with each participant. For data analysis, the Iramuteq software was used, developed for analysis of textual corpus, for later thematic analysis. Results and Discussion: Through the systematization of the data performed by the software, 04 thematic classes were built: Palliative Care: focus on the hospital environment; Palliative Care in Primary Care: challenges and possibilities for health practice; Palliative Care Indications: the perspective of the interprofessional team; The basics are not what is necessary: ​​for training with more information. The association between Palliative Care and the hospital environment is still very present in the speeches of the participants, due to the approximation of this theme with terminally ill patients. Allied to this, the superficial knowledge on the subject, also due to a low approach of this in undergraduate and graduate courses in the health area, makes the early identification of patients with indication for Palliative Care to be impaired. Facilitators and barriers were found for the practice of Palliative Care in the Primary Health Care. The very constitution of this scenario, with its characteristics such as team care, proximity to the territory, bond, humanized care, comprehensive care are fundamental points to see palliative care where it certainly already exists. Final considerations: The present study suggests that this theme needs to be present in curricula of courses in the health area, not in a superficial way, but being approached with its real importance. It is necessary to talk about incurable diseases, about alleviating suffering and about finitude. The study presented limitations, as it was restricted to some health units in a municipality. Thus, it is suggested that more studies be developed on this topic, in order to improve the quality of care for patients with indication of such care.